Peningkatan Minat dan Hasil Belajar IPA Melalui Metode Eksperimen Pada Materi Rangkaian Listrik di Kelas IX SMPN 1 Percut Sei Tuan - Syofia Yohana (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
This research was conducted on the basis of the results of observations of the science learning process in class, where the interests and learning outcomes of science learning, especially in class IX-3 have not progressed as expected. Low learning interest causes the students' daily test scores to show disappointing results, where the results have not reached the expected Minimum Completeness Criteria standard. The average value of science learning outcomes in grades IX -3 at SMP Percut Sei Tuan only reached 55.1. To overcome this problem, it is necessary to improve by conducting Classroom Action Research. Action research was conducted in class IX-3 SMP Negeri 1 Percut Sei Tuan Jln.Besar Tembung Gang Pendidikan, Percut Sei Tuan District, Deli Serdang Regency. The research lasted for 3 months in the odd semester of the 2017/2018 school year which was carried out in 2 cycles by suggesting 4 stages for each cycle, namely: the planning, implementation, observation and reflection stages. The data obtained from each cycle were analyzed using qualitative and quantitative data analysis. This can be seen from the results of the average observation of student interest in learning science per individual, where students with very high interest in learning are 3.13%, students with high interest categories are 46.87%, students who are interested in learning are 34.37% and students with low interest in learning are 15.63%. Overall, the percentage of interest in learning has not reached 75%. Then continued with the second cycle, it was obtained that the observation interest in learning had increased. This was seen from the results of the average observation of student interest in learning science per individual that had increased. where students with very high interest in learning categories 25% of students with high interest categories 66.67%, students with sufficient interest in learning categories 8.33% overall the percentage of interest in learning has reached above 75%. The results of the first cycle test, there were 24 students (66.67%) who had achieved mastery learning while 12 students (33.33%) had not yet achieved mastery learning. After it is known that there is an increase, it is continued to provide action in cycle II. The results of the second cycle test had increased, the number of students who completed was very large, namely from 36 students, it turned out that 33 students (91.67%) had achieved completeness in learning, only 3 students (8.33%) had not achieved completeness in study.